2020
DOI: 10.2147/dmso.s242585
|View full text |Cite
|
Sign up to set email alerts
|

<p>Deep Learning-Based Method of Diagnosing Hyperlipidemia and Providing Diagnostic Markers Automatically</p>

Abstract: Introduction: The research of auxiliary diagnosis has always been one of the hotspots in the world. The implementation of auxiliary diagnosis support algorithm for medical text data faces challenges with interpretability and creditability. The improvement of clinical diagnostic techniques means not only the improvement of diagnostic accuracy but also the further study of diagnostic basis. Traditional research methods for diagnostic markers often require a large amount of time and economic costs. Research objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…All three models outperformed the clinical standard Dutch Lipid score in both cohorts. Similar findings have been produced for hyperlipidemia, where Liu et al trained an LTSM network on 500 EHR samples [21]. The model achieved an ACC score of 0.94, an AUC score of 0.974, a sensitivity of 0.96, and a specificity of 0.92.…”
Section: Hypercholesterolemiasupporting
confidence: 57%
“…All three models outperformed the clinical standard Dutch Lipid score in both cohorts. Similar findings have been produced for hyperlipidemia, where Liu et al trained an LTSM network on 500 EHR samples [21]. The model achieved an ACC score of 0.94, an AUC score of 0.974, a sensitivity of 0.96, and a specificity of 0.92.…”
Section: Hypercholesterolemiasupporting
confidence: 57%
“…Traditionally, the theory that increasing HDL-C to higher levels is more conducive to reducing cardiovascular diseases and adverse events is being questioned by researchers [ 33 , 34 ]. Some scholars have even suggested that reducing HDL-C is more valuable in certain patients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further increase the auxiliary ability of the model to a certain extent, we also explored what physiological parameters affect the AI model to infer treatment strategies. An attention-based LSTM model is used to analyze the abovementioned influencing factors (Liu et al 2020). The patient's physiological parameters are input, and the model outputs the discrete actions of the doctor or the AI model for the VP dose.…”
Section: Providing Treatment Strategiesmentioning
confidence: 99%